2014
DOI: 10.1051/0004-6361/201322343
|View full text |Cite
|
Sign up to set email alerts
|

A characteristic oxygen abundance gradient in galaxy disks unveiled with CALIFA

Abstract: We present the largest and most homogeneous catalog of H ii regions and associations compiled so far. The catalog comprises more than 7000 ionized regions, extracted from 306 galaxies observed by the CALIFA survey. We describe the procedures used to detect, select, and analyze the spectroscopic properties of these ionized regions. In the current study we focus on characterizing of the radial gradient of the oxygen abundance in the ionized gas, based on the study of the deprojected distribution of H ii regions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
289
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(330 citation statements)
references
References 165 publications
38
289
2
Order By: Relevance
“…We repeated the analysis restricting the selection to those spaxels with an EW(Hα) > 20Å without any significant variation in the results. Figure 4 illustrates these results, showing the common abundance gradient (left panel), very similar to the one reported in [44], and the different shapes in the abundance profile at different masses (right panel), where the three regimes described before are evident. For this particular case, the O3N2 calibrator proposed by [49] was adopted (12 + log(O/H) = 8.50 − 0.22 log(O3N2)).…”
Section: Results Of Our Studies Of the H II Regionssupporting
confidence: 74%
See 1 more Smart Citation
“…We repeated the analysis restricting the selection to those spaxels with an EW(Hα) > 20Å without any significant variation in the results. Figure 4 illustrates these results, showing the common abundance gradient (left panel), very similar to the one reported in [44], and the different shapes in the abundance profile at different masses (right panel), where the three regimes described before are evident. For this particular case, the O3N2 calibrator proposed by [49] was adopted (12 + log(O/H) = 8.50 − 0.22 log(O3N2)).…”
Section: Results Of Our Studies Of the H II Regionssupporting
confidence: 74%
“…In [44], we used the updated CALIFA catalog of ∼7000 H II regions, extracted from 306 individual galaxies, to study the radial oxygen abundance gradient up to 3-4 disk effective radii. We confirmed that the abundance gradients present a common slope up to ∼2 effective radii, with a distribution compatible with being produced by random fluctuations, for all galaxies when normalized to the disk effective radius of α O/H = −0.1 dex/r e (using the O3N2 calibrator by [42]).…”
Section: Results Of Our Studies Of the H II Regionsmentioning
confidence: 99%
“…Cano-Díaz et al (2016) showed that the relationship between star formation rate (SFR) and stellar mass that held for entire star-forming galaxies was also true for spatially resolved regions within a galaxy. In another intriguing clue to the relation between small and large scales, Sánchez et al (2014) found that the H II regions in 306 CALIFA galaxies have a characteristic disk oxygen abundance gradient when scaled to its effective radius.…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%
“…The gas-phase metallicity has been studied in the Milky Way and nearby spiral galaxies through abundance analysis of H II regions (e.g., Vila-Costas & Edmunds 1992; Sánchez et al 2014), disclosing that a radial metallicity gradient across the galactic disk is almost invariably negative (i.e., higher abundances near the galactic center). The oxygen metallicity gradient is a key constraint to models of chemical evolution.…”
Section: Introductionmentioning
confidence: 99%